Label-free electrochemical immunosensor as a reliable point-of-care device for the detection of Interleukin-6 in serum samples from patients with psoriasis - Cancelliere, Rocco; Cosio, Terenzio; Campione, Elena; Corvino, Martina; D’Amico, Maria Pia; Micheli, Laura; Signori, Emanuela; Contini, Giorgio (Frontiers in Chemistry, 2023)
Interleukin-6 (IL-6) plays a crucial role in autoimmunity and chronic inflammation. This study aims to develop a low-cost, simple-to-manufacture, and user-friendly label-free electrochemical point-of-care device for the rapid detection of IL-6 in patients with psoriasis. Precisely, a sandwich-based format immunosensor was developed using two primary antibodies (mAb-IL6 clone-5 and clone-7) and screen-printed electrodes modified with an inexpensive recycling electrochemical enhancing material, called biochar. mAb-IL6 clone-5 was used as a covalently immobilized capture bioreceptor on modified electrodes, and mAb-IL6 clone-7 was used to recognize the immunocomplex (Anti-IL6 clone-5 and IL-6) and form the sandwich. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were used to conduct electrochemical characterization of the layer-by-layer assembly of the immunosensor, while square wave voltammetry (SWV) was used to perform the sensing. The developed immunosensor demonstrated robust analytical performance in buffer solution, with a wide linear range (LR) by varying from 2 to 250 pg/mL, a good limit of detection (LOD) of 0.78 pg/mL and reproducibility (RSD<7%). In addition, a spectrophotometric ELISA kit was employed to validate the results obtained with the label-free device by analyzing twenty-five serum samples from control and patients affected by psoriasis. A strong correlation in terms of pg/mL concentration of IL-6 was found comparing the two methods, with the advantage for our label-free biosensor of an ease use and a quicker detection time. Based on IL-6 levels, the proposed immunosensor is a dependable, non-invasive screening device capable of predicting disease onset, progression, and treatment efficacy.